Occurrence of dioctophymosis in canines within a riparian zone of the Río de la Plata watercourse, in Ensenada, Buenos Aires Province, Argentina - Radman, Nilda Ester (2017)
Dioctophymosis is a parasitic disease occasioned by the so-called "giant kidney worm", Dioctophyme renale, a nematode with an indirect life cycle. This parasite´s definitive host is the mink, Mustela vison, though numerous wild and domestic mammals as well as man can serve as final hosts. The worms also can be in ectopic locations in the body. We surveyed 692 canines by ecography, urine sampling, surgery, necropsy, and clinical examination and diagnosed 244 cases of dioctophymosis (35.3%). Of the cases of dioctophymosis identified, 30.7% were obtained by ecography, 45.9% by urinalysis, and 17.6% by both those techniques -in addition to positive findings through surgery (2.5%), necropsy (2.5%), and the spontaneous elimination of the parasites (0.8%). Cases of dioctophymosis were observed in animals as young as 4 months of age up to 15 years. The frequency of D. renale diagnosis throughout the sampling period varied significantly. There was a statistically significant association between risk factors (swimming in the river, eating frogs, fish or eels, drinking ditch water) and the prevalence of infection. It was discussed the period missing after infection in canines.